Role of crushed skeletal muscle extract in hemostasis. Issue 5 (27th February 2015) - Rajiv, Sukanya; Rodgers, Susan; Bassiouni, Ahmed; Vreugde, Sarah; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Use of muscle grafts for hemostasis during surgery has re‐emerged; recent animal model studies have shown effective bleeding control with their use. However, the mechanism of action is unknown. The aim of this study is to evaluate the action of muscle extracts on the coagulation pathways and platelet aggregation. Methods Muscle extracts were prepared by dissolving crushed snap‐frozen muscle tissue (0.04 to 0.8 mg) in 1 mL saline. Saline was used as control. Prothrombin time, activated partial thromboplastin time (APTT), thrombin time, and platelet aggregation studies were performed on both muscle extract and saline. Prothrombin time and APTT were repeated using factor VII–deficient plasma, factor X–deficient plasma, lupus plasma, and contact pathway–inhibited plasma. Mean readings in the muscle group and control group were compared using nonparametric Mann‐Whitney U test (Wilcoxon rank sum test with continuity correction). Results Among the various coagulation parameters, there was no significant difference between saline and muscle (p > 0.05), except in the APTT using factor X–deficient plasma (mean APTT 133.89 seconds and 185.10 seconds for muscle and saline, respectively; p < 0.0001). Higher concentrations of the muscle extract (>0.5 mg/mL) increased platelet aggregation from 23.9% to 85.5% (p = 0.0001). Conclusion Platelet aggregation plays a role in the hemostatic efficacy of muscle grafts. Even though action on the coagulation pathway via APTT is statistically significant, clinical significance may be low.